Expresividad poética y traducción con breve lectura de Fedro, I. 1 (Argos, 2025)
The term “poetic expressiveness” refers to the multiple joints of the plan ofexpression, derived from the expressive value of the linguistic sign (Rosset:1970, 135) and its particular role in the field of poetry. The features ofmeaning, such as projection, elevation and salience, make it possible toconsider expressive all poetic statements which constitute particularlydense instances in the formal consolidation of a convergence betweenthe two planes (expression/content), and therefore it stands out from theothers due to the high density of structural parallelisms and isomorphisms,which are procedures responsible for the impression that a particular form of content can only be expressed by cutting that same specific form ofexpression out. These considerations have an immediate impact on thereading, interpretation and practice of translating poems, which is intendedto be demonstrated here, through an example of translation of a Phaedrus’fable, written in iambic meter.